Efektivitas Media Pembelajaran Infografis Materi Bencana Banjir di Kelas IV SDN Petamburan 05, Kelurahan Petamburan, Jakarta Pusat - Zain, Kireina Oemardi Larasati; Muzani, Muzani; Munandar, Aris (Jurnal Ilmiah Wahana Pendidikan, 2024)
The lack of use of learning media resulted in the teaching and learning process being less effective. Apart from the lack of learning support, SDN Petamburan 05 is also one of the elementary schools in Petamburan Village, which is located in a flood-prone area. Learning media in the form of infographics is one of the media where large amounts of data can be easily understood and remembered, by utilizing visualization. This study aims to determine the level of effectiveness of using infographics in learning flood disaster material. This study uses a quasi-experimental research type (quasi-experimental design) in the form of Nonequivalent Control Group Design, which involves two groups or classes that are not selected randomly or through purposive sampling. Based on the sampling, it was obtained that class IV A as the experimental class was given treatment in the form of learning using infographic media and class IV B as the control class with conventional methods. The findings of this study indicate that the average learning outcomes of the experimental class with learning using infographic media are significantly higher than the control class which only uses the lecture method. In the experimental class the average pre-test score was 70.00, and the average post-test score for the experimental class was 87.11, while in the control class the average pre-test score was 69.77, and the average the average post-test score was 80.68. The results of the Independent Sample T- Test test show that there is a significant difference between the pre-test and post-test scores, with a significance value of 0.038 or 0.05 and the results of t table > t arithmetic, or 2.136 > 2.013, which indicates that H0 is rejected and Ha accepted. Based on the analysis using the N-Gain test, the use of infographic learning media on flood disaster material in the experimental class was declared quite effective with a value of 58.7841 percent, while it was not effective in the control class with a value of 36,0049 percent.